Facing The Independent Curriculum: Teacher Challenges And Strategies In The Evaluation Of Islamic Religious Education Learning - Ruslan Ruslan; Neneng Faijah; Luthfiyah Luthfiyah; Khuloud Mustafa Alouzi (At-Tarbiyat, 2024)
This research is intended to find out the practices and challenges of teachers in PAI learning evaluation on independent curricula in SMAN 1 City of Bima. This qualitative research uses data sources from PAI teachers, students, and the deputy head of school in the curriculum field. In addition to the primary sources, the research uses secondary sources such as journals and related books. Data collection techniques include interviews, observations, and documentation. The results of this research show that PAI learning evaluation practice on the curriculum is independent in SMAN 1 City of Bima initially by compiling RPP before learning, performing initial formative assessment, formative evaluation during the learning process, and finally performing summary assessment in the form of daily evaluation, mid-semester assessments, projects, and final evaluation of semesters. The challenges in the evaluation of learning on the independent curriculum are the limitations of the teacher's skills in using the beesmart application, the incomprehensible implementation of the independent Curriculum, the convenience of educators using old curricula, the equalization of paradigms of thinking that school citizens are willing to accept changes, the limitation of funds in P5 maintenance, educators suffering from overdose applications, the difficulty of improving the critical character of pupils, and the difficulties of measuring the initial abilities of heterogeneous pupils. This research is limited to PAI learning evaluation aspects on an independent curriculum. Of course, there are many other aspects that can be studied by other researchers, such as materials, methodologies, learning media, and other things related to the independent curriculum in PAI learning.